[(Di-o-tolylphosphino)methyl]diphenylphosphine sulfide - Priyanka P. Pitroda; Ansonia H. Badgett; Geralyn A. Dickey; Danielle L. Gray; Quinetta D. Shelby (Acta Crystallographica Section E, 2009)
In the title compound, C27H26P2S, the P—C—P angle is 114.33 (13)°. The bond distances are longer and the bond angles are smaller at the P atom bonded to the o-tolyl groups owing to the presence of a lone pair of electrons. One phenyl ring is disordered over three sites [occupancies 0.317 (8), 0.250 (8), and 0.433 (6)] and the other phenyl ring is disordered over two sites [occupancies 0.871 (6) and 0.129 (6)].